2020
DOI: 10.3389/fpls.2020.00232
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Proteins AtNHR2A and AtNHR2B Are Multi-Functional Proteins Integrating Plant Immunity With Other Biological Processes

Abstract: AtNHR2A (Arabidopsis thaliana nonhost resistance 2A) and AtNHR2B (Arabidopsis thaliana nonhost resistance 2B) are two proteins that participate in nonhost resistance, a broad-spectrum mechanism of plant immunity that protects plants against the majority of potential pathogens. AtNHR2A and AtNHR2B are localized to the cytoplasm, chloroplasts, and other subcellular compartments of unknown identity. The multiple localizations of AtNHR2A and AtNHR2B suggest that these two proteins are highly dynamic and versatile,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…In-gel trypsin digestion and mass spectrometry were performed as previously described (Singh et al, 2020). Each lane was cut into five pieces, each covering a range of molecular weights.…”
Section: In-gel Trypsin Digestionmentioning
confidence: 99%
“…In-gel trypsin digestion and mass spectrometry were performed as previously described (Singh et al, 2020). Each lane was cut into five pieces, each covering a range of molecular weights.…”
Section: In-gel Trypsin Digestionmentioning
confidence: 99%
“…100 mg of dissected inflorescence tissues of pPDF1::FLAG-ATML1 X pATML1::mCitrine-ATML1 (F1 generation) plants including flower buds up to stage 8-9 of flower development were used for protein extraction and Co-IP as described in ( 73 ) with modifications in antibodies used. In short, we used EZview red ANTI-FLAG M2 affinity gel (Sigma Cat #F2426 lot #SLBN6224V) according to the manufacturer’s protocol to bind the FLAG-ATML1 protein and washed it with stringent washing buffer conditions to remove the non-specific binding proteins.…”
Section: Methodsmentioning
confidence: 99%
“…Atnhr2b mutant plants are immunocompromised, and as a result, they are susceptible to pathogens that normally do not cause disease in wild-type plants, called non-adapted pathogens (31). We further showed by live-cell imaging that AtNHR2B tagged with the green fluorescent protein (GFP) localizes to chloroplasts and compartments of the endomembrane system (31), and through proteomics approaches, we also showed that AtNHR2B interacts with proteins localized to chloroplasts, mitochondria and nucleus (32). Until now, it was not known if AtNHR2B was targeted by pathogen virulence factors.…”
Section: Introductionmentioning
confidence: 90%